The Role and Mechanism of Metformin in Inflammatory Diseases - Lin H; Ao H; Guo G; Liu M (Dove Medical Press, 2023)
Huan Lin,1 Haiyong Ao,2 Guanghua Guo,1 Mingzhuo Liu1 1Medical Center of Burn Plastic and Wound Repair, The First Affiliated Hospital of Nanchang University, Nanchang, People's Republic of China; 2Jiangxi Key Laboratory of Nanobiomaterials & School of Materials Science and Engineering, East China Jiaotong University, Nanchang, Jiangxi, People's Republic of ChinaCorrespondence: Guanghua Guo; Mingzhuo Liu, Medical Center of Burn Plastic and Wound Repair, The First Affiliated Hospital of Nanchang University, Medical Center of Burn Plastic and Wound Repair, The First Affiliated Hospital of Nanchang University, No. 17, Yongwai Zheng Street, Nanchang, Jiangxi, People's Republic of China, Tel +8613007222275 ; +8615879093602, Email ndyfy00655@ncu.edu.cn; ndyfy05397@ncu.edu.cnAbstract: Metformin is a classical drug used to treat type 2 diabetes. With the development of research on metformin, it has been found that metformin also has several advantages aside from its hypoglycemic effect, such as anti-inflammatory, anti-aging, anti-cancer, improving intestinal flora, and other effects. The prevention of inflammation is critical because chronic inflammation is associated with numerous diseases of considerable public health. Therefore, there has been growing interest in the role of metformin in treating various inflammatory conditions. However, the precise anti-inflammatory mechanisms of metformin were inconsistent in the reported studies. Thus, this review aims to summarize various currently known possible mechanisms of metformin involved in inflammatory diseases and provide references for the clinical application of metformin.Keywords: metformin, AMPK, inflammation, mechanisms